O significado da educação de jovens e adultos para educandos e educadores no CEJA Cesário Neto - Araujo, Zilma Franco Morais (2013)
The research investigated the meaning of the Teens and Adults Education has for learners and educators from the I Segment-Fundamental School, from the implantation of the EJA Centers (CEJA) in Mato Grosso, as a result of questions and reflections about the education model that is written and inscribed there. The method of approach used was the phenomenological. Phenomenology is a specific way to look at phenomena unveiling meanings that in dialog with its dimensions causes us an oncoming of speaking and doing. We know that teaching does not exist without learning and this is, therefore, a complementary relationship. In it, the valorization of the meaning will be representative of the modality. These meanings show that when languages soaked by the aura of knowledge and boldness of "being more" intersect, new faces of reality emerge in opposition to the educational dichotomies, confronting it, and these, when in a world that makes the subjects invisibles, makes them visible. In Paulo Freire, educating is a demanding "doing", and in this moment, the intersection of meanings allows for a connection of the world of the subjects- that only listen, to the school world- that only speaks. World in transit of a body, illiterate, to a world of this same body, now literate, willing to a new pronounce. And, in that way, at the same time that the protagonists are unveiled, they also unveil the pedagogical function in the school environment.